Arqueologia - Laclos, Frédéric Fruteau de (Mnemosine, 2015)
Tradução de DE LACLOS, F. F. Archéologie. In: BERT, J.-F. & LAMY, J. Michel Foucault: un héritage critique. Paris: CNRS, 2014, p. 89-95. Tradutor: Alessandro Francisco.